Academic expectations among international students from North-Western China: A case of technology use during and post COVID-19 - AL-Qadri, Abdo Hasan; Ahmed, Salah A. M.; Suliman, Mohammed A. E.; Al-khresheh, Mohammad H.; Boudouaia, Azzeddine; Zhao, Wei; Zhang, Wenlan (Frontiers in Psychology, 2022)
This study examines the influence of the COVID-19 crisis on international students' academic expectations of learning outcomes resulting in North-Western China. COVID-19 emergence has resulted in several dramatic shifts in educational activities that have moved from traditional to online or hybrid modes. Hence, investigating international students' academic expectations with the interactions of adopted technologies is a topic addressing the current scenario and challenges. A mixed approach, comprising two different instruments (questionnaire and interview), was followed to achieve this primary objective. While a questionnaire was carried out on 551 international students, divided into two different groups, ten students were interviewed during and after the lockdowns. The findings revealed that COVID-19 had a significant impact on the academic expectations of students along with various factors, including training for employment, personal and social development, international student mobility, motivation, social pressure, and social interaction with the role of supporting technologies. In terms of gender, males outperformed better than females in motivation, social interaction, training for employment, and personal and social development factors. Based on these findings, a group of recommendations was put forward.